Assessing financial management capacity for district health system development : a case study of the Mount Frere District - Morar, Reno Lance (Health Economics Unit, 2017)
The specific objective of this report is the assessment and analysis of the current financial management capacity at the district level in Mount Frere. It will specifically address the assessment and analysis of financial management capacity in the Mount Frere district, Region E in the EC Province, Department of Health.